The Effectiveness of Google Classroom on the First Semester Students’ Writing Skill at STKIP PGRI Tulungagung - Ika Rakhmawati (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2020)
This research investigates whether the students achieve better Writing skill after being taught using google classroom or not. The design of this research is quantitative research, which is concerned with hypothesis, formulation, testing and analysis of the relationship between two variables; dependent variable and independent variable. Both of variables are selected  and observed.Based on the statistical calculation using SPSS 16.0, the researcher gave interpretation to significant value. Because significant value 0.000 was smaller than significant level 0.05, it can be concluded that alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. It means that there was significant effect after using Google classroom to teach writing. Thus, it can be concluded that by using Google classroom in teaching writing at the first semester at STKIP PGRI Tulungagung in the academic year of 2018/2019 is effective.As the conclusion, teaching writing by using Google classroom is more effective and interesting for the first semester students at STKIP PGRI Tulungagung in the academic year 2018/2019.  By using google classroom, students hopefully can increase their Writing skill. Teachers should give motivation to students so that they will be more interested in learning activity. The researcher hopes that this study will be useful for the further researchers to conduct the similar research that deals with the same media, and with the same or different research design to develop the teaching quality of writing skill by using Google classroom.